Evaluasi Pembelajaran Nilai-Nilai Keislaman di Sekolah Dasar Plus Rahmat Kediri Perspektif Logic Model - Tsani, Iskandar; Sufirmansyah, Sufirmansyah (Belajea: Jurnal Pendidikan Islam, 2024)
This article aims to evaluate the learning of Islamic values at SD Plus Rahmat Kediri from a logic model perspective. This article is based on mixed method field research. The qualitative approach is maximized to collect data from a number of key informants through interviews, observation, and documentation. While the descriptive-quantitative approach is utilized to see how much outcome is produced. Then, the data is analyzed interactively through the stages of data collection, data reduction, data display, and conclusion drawing. This article concludes that the input of learning Islamic values at SD Plus Rahmat Kediri structurally involves the Korbid (Field Coordinator) of the School, especially the Faith and Taqwa Field, the Facilities and Infrastructure Field, the Grade Level Coordinator, Classroom Teachers and Homeroom Teachers, the Ummi Learning Session Coordinator, and the ustadz/ustadzah from the Ummi Foundation. Culturally, the school climate at SD Plus Rahmat Kediri is very good, as manifested in the academic field, community aspect, security aspect, and institutional environment. The morning muroja’ah activity has an impact on the emergence of the Islamic values of ta’addub, qudwah, and i’tidal. BTQ tutoring in the Ummi method produces the Islamic values of tathawwur wa ibtikar, qudwah, and i’tidal. The dhuha and dhuhur prayer congregation activities bring out the Islamic values of ta’addub, qudwah, and shura. The activities of clean friday and blessed friday bring out the Islamic values of musawah, ta’addub, tathawwur wa ibtikar, and tasamuh.